Evaluation of a School-Based Asthma Education Protocol: Iggy and the Inhalers. (June 2017) - Mickel, Catherine F.; Shanovich, Kathleen K.; Evans, Michael D.; Jackson, Daniel J.
School-based asthma education offers an opportunity to reach low-income children at risk for poor asthma control. Iggy and the Inhalers (Iggy) is an asthma education program that was implemented in a Midwest metropolitan school district. The purpose of this evaluation was to conduct a comprehensive program evaluation. Objectives included increasing children's asthma-related knowledge and families' awareness of asthma management, while cultivating collaboration between school nurses and asthma providers. A total of 173 students participated in Iggy education, with 147 completing both initial and 1-month posttests. Thirty-one parents and seven school nurses provided qualitative feedback. Iggy was well received by children, parents, and school nurses. Asthma knowledge increased significantly ( p < .001) between pretest and posttest, and this increase was retained at 1-month follow-up. This program evaluation suggests that our program had a significant, sustained impact on students' asthma knowledge. It also supports the value of collaboration between asthma providers and school nurses.